The factors affecting the willingness to pay for organic fertilizers of banana growers in Davao Del Norte - De Lumban, Nisa Lianca D.
Consumers worldwide are becoming more health-conscious nowadays. Given this fact, the demand for organic fertilizer is expected to increase in proportion to the increase in the demand for organic food products. The researcher attempted to explore the factors that affect the willingness of the banana growers to pay for organic fertilizers, as such knowledge may help push the widespread adoption of the more sustainable, environmentally-sound organic farming practices among banana growers. In this study, various factors may possibly have a significant effect on the willingness to pay for organic fertilizers were assessed. The factors considered were the attitudinal factors (i.e. towards price, availability and accessibility of organic fertilizers, labor costs for production, agricultural practices), and awareness factors (towards organic agriculture, sustainable agriculture, pesticide residues, soil erosion). Demographic information was also gathered to provide a profile of the respondents in the study. In general, the respondents know little about organic fertilizers, organic agriculture, effects of commercial fertilizers, soil erosion and the causes for it. It was detemined that of all the explanatory variables used the model, only one variable was statistically significant in explaining the outcome of the dependent variable, which is if the growers were willing to play given that there are higher labor costs for production. The study recommends that a wider scope of area shall be included in the sampling of the study, since this study only covered two municipalities of Davao del Norte. Also, the researcher recommends that further research be done on organic fertilizers regarding the formulation of the components essential for fertilization, and application technologies which could help lessen the labor costs incurred in production.
Thesis, Undergraduate (BS in Agribusiness Economics)--U.P. Mindanao